Comparison of flexible ureteroscopy and mini-percutaneous nephrolithotomy in the treatment for multiple nephrolithiasis - Lv, Guangda; Zhang, Zhiwei; Du, Fei; Qi, Wenqiang; Zhong, Minglei; Zhou, Yongheng; Zhou, Changkuo; Li, Yan; Zhang, Dongqing (Frontiers in Surgery, 2022)
Objective To compare the outcomes of flexible ureteroscopy and mini-percutaneous nephrolithotomy in the treatment for multiple nephrolithiasis in 1-2cm size. Methods The clinical data of patients with multiple renal calculi in the range of 1-2CM who underwent flexible ureteroscopy lithotripsy and percutaneous nephrolithotomy in Qilu Hospital of Shandong University from January 2016 to March 2021 were retrospectively collected and matched using propensity score matching. Then a subgrouping of the number of stones was performed. Patients were divided into Group A and Group B according to their stone numbers. Patients with no statistically significant differences in baseline data were matched to compare the safety and efficacy of the two procedures. Results A total of 210 patients with clinical data were collected, and the patients' baseline data were not comparable, and 142 patients were finally included in the study after propensity score matching. There was no statistical difference in baseline data between the two groups of patients. The postoperative hospital days (3.00, 2.00 VS 7.00, 3.00, P<0.001), operation time (90.00, 50.00 VS 110.00, 53.00, P=0.018), complications (6, 6.8% VS 14, 25.9%, P=0.001) of patients in flexible ureteroscopy group %, P=0.001) was significantly lower than that in the percutaneous nephrolithotomy group. There was no significant difference in stone clearance rate between the two groups (76, 86.4% VS 42, 77.8%, P=0.185). When the number of stones was no more than 3, the operation time (85.00, 49.00 VS 110.00, 53.00, P=0.005) and complications (2, 4.2% VS 11, 29.7%, P=0.001) of f-URS were significantly less than those of mPCNL, but when the number of stones was more than 3, there was no significant difference between the two operations. Conclusion For multiple nephrolithiasis within 1-2CM, when the number of stones does not exceed 3, flexible ureteroscopy can achieve the same stone clearance rate as percutaneous nephrolithotomy, while having shorter post-operation days, operative time and fewer complications. When the number of stones is more than 3, there are no significant difference between two operations.